Internet Business: How Perception of Benefits, Risks, and Ease in Decision Making - Bahari, Andi Faisal; Basalamah, Jafar; Ashoer, Muhammad; Syahnur, Muh. Haerdiansyah (Jurnal Manajemen Bisnis, 2021)
Research aims: The reason for this examination is to decide the temporary, semi-dominant, and dominant effects of the three independent factors, in particular the perception of benefits, risks, and ease on the dependent variable, specifically decision making in e-commerce.Design/Methodology/Approach: The methodology used was a purposeful examination method, in which the testing focuses on particular qualities or characteristics considered to be communicated to the population or have certain qualities according to the issues raised. The total sample was 60 participants from the announcement through Joseph F. Hair’s theory, whereby the number of tests used in non-like evaluations varied from 15 to many times that of the exogenous factors.Research findings: The study findings have consequences in two principal aspects, both management consequences for online products/service suppliers, which provide an empirical picture of the need to constantly balance the ease and benefit factors of online market and package unit requirements of the same urgency.Theoretical contribution/Originality: This research was carried out to explore and examine customer decision-making in using the internet about their perception of benefits, risks, and ease of using it.Research limitation: This research has advantages for the online marketplace to know how customers perceive their product or services.